The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0ew00314j
|View full text |Cite
|
Sign up to set email alerts
|

The impact of biofilm thickness-restraint and carrier type on attached growth system performance, solids characteristics and settleability

Abstract: The moving bed biofilm reactor (MBBR) technology is a proven standalone and add-on technology for carbon and nutrient removal from municipal wastewaters. The key challenge of the carbon removal MBBR...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This indicates that the testing period of 3 weeks is not adequate to achieve the required biodegradation rate of biomass. Arabgol et al [ 27 ] reported that five weeks of operation are required for full inoculation of MBBR, followed by another three weeks for reaching steady-state operation. In the case of BOD 5 , the removal efficiency varied from 89% to 95%.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the testing period of 3 weeks is not adequate to achieve the required biodegradation rate of biomass. Arabgol et al [ 27 ] reported that five weeks of operation are required for full inoculation of MBBR, followed by another three weeks for reaching steady-state operation. In the case of BOD 5 , the removal efficiency varied from 89% to 95%.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm mass was measured using a protocol described and modified by Delatolla et al (2008) , Ren et al (2016) , Schopf et al (2018) , and Arabgol et al (2020) . Biofilm carriers were harvested from MBBR reactors P N1 and P N2 and dried at 105°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…3,20 Although the bio-carriers provide protection for the microbial community, a large amount of biofilms are still shed due to the aeration and the complex water flow in the MBBR, which affects its water treatment capacity. [21][22][23] This symptom has been greatly alleviated by the modified bio-carriers, which can promote the adhesion of microorganisms and accelerate the formation of biofilms. 5,20,24 Moreover, using EC technology to assist the MBBR start-up has become more popular recently.…”
Section: Introductionmentioning
confidence: 99%